Ouverture et croissance industrielle en Chine Etude empirique sur un échantillon de villes - Démurger, Sylvie (OECD Publishing, 1995)
This study concerns the impact of China's "opening and reform" policies on short-term urban industrial growth. It seeks to detail differences in inter-urban growth by observing different degrees of opening and the implementation of reforms. The study also seeks to identify phenomena of inter- and intra-urban growth spillovers. The econometric analysis uses a database of the principal economic developments in 434 Chinese towns over the period 1988 - 1991. The results highlight two main mechanisms by which opening has affected growth performance. These mechanisms are access to foreign technology and the positive externalities on total regional production engendered by exports ...
Keywords: Development; China, People's Republic